Leveraging Factors of Self-Efficacy and Motivation to Optimize Stroke Recovery - Gangwani, Rachana; Cain, Amelia; Collins, Amy; Cassidy, Jessica M. (Frontiers in Neurology, 2022)
The International Classification of Functioning, Disability and Health framework recognizes that an individual’s functioning post-stroke reflects an interaction between their health condition and contextual factors encompassing personal and environmental factors. Personal factors significantly impact rehabilitation outcomes as they determine how an individual evaluates their situation and copes with their condition in daily life. A key personal factor is self-efficacy¬– an individual’s belief in their capacity to achieve certain outcomes. Self-efficacy influences an individual’s motivational state to execute behaviors necessary for achieving desired rehabilitation outcomes. Stroke rehabilitation practice and research now acknowledge self-efficacy and motivation as critical elements in post-stroke recovery, and increasing evidence highlights their contributions to motor (re)learning. Given the informative value of neuroimaging-based biomarkers in stroke, elucidating the neurological underpinnings of self-efficacy and motivation may optimize post-stroke recovery. In this review, we examine the role of self-efficacy and motivation in stroke rehabilitation and recovery, identify potential neural substrates underlying these factors from current neuroimaging literature, and discuss how leveraging these factors and their associated neural substrates has the potential to advance the field of stroke rehabilitation.